Efficacy and prognosis of preoperative radiation in progressive tongue cancer - MITANI, Hiroki; YONEKAWA, Hiroyuki; KAWABATA, Kazuyoshi; MIURA, Kouki; YOSHIMOTO, Seiichi; KAMATA, Shin-etsu; BEPPU, Takeshi; KIMURA, Yukinori (OTOLOGIA FUKUOKA, 2004)
It is clinically experienced that preoperative treatments such as chemotherapy and radiotherapy or both are given during the period under consideration for surgery in local progressive head and neck cancers. Whether these preoperative treatments are right or wrong is left to the judgement of each hospital. Twenty years have passed since surgical therapy consisting mainly of reconstruction surgery was given as the treatment of progressive tongue cancer at this department. Based on the changes in therapies from the small radiation source therapy in the past, we have given preoperative radiation therapy in many cases. Regarding the efficacy of preoperative radiation as an adjuvant therapy, this paper studies clinical results using 101 cases of T3-T4 tongue cancers as the subjects, for which radiation alone had been given systematically. The appearance rate of the effective cases showing the efficacy of preoperative radiation histologically and the ineffective cases was 55:45. Since a significant difference in the controling rate and survival rate was fixed association was efficacy of radiation contributed controling rate of the but was not effective survival rate with not metastasis rate was found between the two groups, a thought to exist between the and prognosis. Preoperative to the improvement in the primary lesion and neck cancer enough to improve the overall much difference in the remote between the two groups.